(untitled) (Boca Raton, FL, 2007)
The book classifies phosphor materials according to the type of luminescence centers employed or the class of host materials used and interprets the optical properties of these materials, including their luminescence characteristics and mechanisms. Placing a strong emphasis on those materials that are important from a practical point of view, the coverage also includes those possessing no possibility for practical use but are important from a theoretical standpoint.
Vật liệu huỳnh quang
Keywords: Phosphors.,Phốt pho